PRODUCTION AND MAINTENANCE OF AFFECTIVE COMMITMENT: RECRUITMENT, SELECTION, AND SOCIALIZATION (Academia Science Repository, 2023)
This article covers the production and maintenance of affective commitment starts at the recruiting stage and within the initial experience of the organization. Social interaction activities that rely on corporate principles which provide constructive role reinforcement at the management level have had an impact on the affective contribution of new recruits to the organization